Preparation method and application of dual-crosslinking ultrasonic response hyaluronic acid hydrogel

The mechanical strength and biocompatibility of hydrogen hydrogel are improved through dual cross -linking strategies, and the accurate release of drugs is achieved through ultrasonic response to solve the lack of existing hydrogel in mechanical strength and drug release control.

CN119345117AActive Publication Date: 2025-01-24NANJING UNIV OF POSTS & TELECOMM

Patent Information

Application Number
CN202411528176.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-30
Publication Date
2025-01-24
Estimated Expiration
2044-10-30

Smart Images

  • Figure CN119345117A_ABST
    Figure CN119345117A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of dual-crosslinking ultrasonic response hyaluronic acid hydrogel, and belongs to the field of drug delivery, the preparation method comprises the following steps: taking hyaluronic acid as a raw material, and preparing hyaluronic acid dopamine through amidation reaction; then synthesizing a block polymer poly (polyethylene glycol metacrylic acid-co-4-vinyl phenylboronic acid) through a copolymerization reaction, mixing the block polymer poly (polyethylene glycol metacrylic acid-co-4-vinyl phenylboronic acid) with hyaluronic acid dopamine, dissolving the mixture in deionized water to obtain a mixed solution, preparing drug-loaded iron oxide nano magnetic microbubbles, adding the drug-loaded iron oxide nano magnetic microbubbles into the mixed solution to obtain a hydrogel solution, adjusting the pH value to 5-6, and standing to obtain the hydrogel. The problems that traditional single hyaluronic acid hydrogel is often insufficient in mechanical strength and elasticity are solved, and the prepared hyaluronic acid hydrogel has excellent mechanical strength and structural stability, can release drugs through ultrasound, has a good release effect, also has the characteristics of low toxicity and good biocompatibility, and can be used for preparing the hydrogel. The method has a good application prospect in the field of biological application.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of drug delivery, and in particular relates to a preparation method and application of a double-crosslinked ultrasound-responsive hyaluronic acid hydrogel. Background Art

[0002] In today's field of biological tissue engineering and drug delivery, the construction of safe and effective tissue engineering and drug delivery systems is of vital importance, and efficient, accurate and safe drug delivery systems have become the focus of research. Drug delivery hydrogel systems have attracted much attention as a potential drug delivery technology. The drug delivery hydrogel system is to load drugs into the gel, and through gel degradation, the release kinetics of the drug can be controlled to improve the bioavailability and stability of the drug. Therefore, the design of the hydrogel is very important. The ideal hydrogel material needs to have good biocompatibility and degradability, and also needs to have a certain strength and hardness, so that the release of the drug can be controlled through different mechanisms of action, such as diffusion, swelling, degradation, etc.

[0003] In the prior art, hydrogel is a type of material with a three-dimensional network structure formed by chemical or physical crosslinking of hydrophilic polymer chains. Its main components include natural polymers (such as hyaluronic acid, chitosan, etc.), synthetic polymers (such as polyacrylamide, polyvinyl alcohol, etc.) and inorganic materials (such as nanoclay, etc.), which can be designed for different types of drug delivery for specific applications. In recent years, hydrogels have been widely used as drug carriers in tissue repair, bone repair, heart regeneration, vascular remodeling and other group engineering. Controlled drug release is a goal that hydrogels usually hope to achieve when delivering stent-type drugs, but due to the huge changes in physiological conditions between the normal microenvironment of the human body and the various diseased parts, ordinary hydrogels as local drug sustained-release systems may not be able to achieve the expected goals in complex pathological microenvironments. In addition, ordinary hydrogels also generally have poor physical properties, such as low mechanical strength, poor biocompatibility, and unstable drug release, which limits their application.

[0004] Among the many hydrogel materials currently used, hyaluronic acid (HA) has become a main material that has attracted much attention in the field of drug delivery because of its unique biocompatibility, biodegradability, good interaction with cells and tissues, and excellent drug release control properties, simulating the physiological conditions of the natural tissue microenvironment. Hyaluronic acid is a polysaccharide that naturally exists in human tissues and has excellent biocompatibility and biodegradability. With its three-dimensional network structure, hyaluronic acid hydrogel can effectively encapsulate various drug molecules and provide a stable storage environment for drugs. Its high water content and soft texture make it compatible with biological tissues, reducing the risk of inducing inflammation and immune rejection. In the process of drug delivery, hyaluronic acid hydrogel can achieve precise control of drug release by adjusting its molecular structure, cross-linking degree and degradation rate. This is crucial for treatments that require long-term sustained release or release of drugs at specific time points. At present, HA has been widely used in the treatment of many diseases, such as arthritis and eye diseases. However, there are still many challenges in practical applications. On the one hand, the mechanical strength of traditional HA hydrogels is often difficult to meet the regulatory requirements, which limits their use in certain application scenarios. On the other hand, the controlled release of drugs in hydrogels is difficult to control the release rate. Existing drug loading methods, such as physical encapsulation and chemical assembly, are difficult to achieve on-demand precise release of drugs, resulting in low drug utilization efficiency and limited therapeutic effects.

[0005] In view of this, the present invention proposes a novel dual cross-linking strategy, which aims to regulate the mechanical strength of the hydrogel so that it can meet higher requirements and realize on-demand drug release that can be controlled by the external field. By introducing a specific cross-linking agent and constructing a complex and stable cross-linking network, not only the mechanical properties of the hyaluronic acid hydrogel are enhanced, but also the precise controlled release of the drug is possible, which is expected to solve the key problems in the current drug delivery field and expand the application scope of hydrogels in the medical field. Summary of the invention

[0006] The purpose of the present invention is to solve the problems of insufficient mechanical strength, poor biocompatibility and difficulty in achieving on-demand precise release of drugs in the hydrogels of the prior art, and to provide a method for preparing a double-cross-linked ultrasound-responsive hyaluronic acid hydrogel. The prepared hydrogel has good biocompatibility and mechanical strength, and can achieve controlled and precise release of drugs.

[0007] The present invention uses hyaluronic acid as the main material, grafts catechol groups onto the main chain of hyaluronic acid through amide reaction for functional modification, introduces boric acid groups into polyethylene glycol methacrylate and catechol to form borate ester bonds as the first crosslink of the gel, and at the same time embeds bubbles loaded with drugs and iron oxide nanoparticles in the gel, and utilizes the covalent action formed by catechol groups and iron oxide nanoparticles as the second crosslink of the gel. The drug-loaded bubbles of iron oxide nanoparticles encapsulated therein act as an ultrasonic response unit, which can cause stable vibration of the bubbles under the action of ultrasound, thereby releasing the drugs and iron oxide nanoparticles on the surface, and realizing ultrasonically controlled drug release of the hydrogel scaffold. The specific scheme is as follows:

[0008] A method for preparing a double-crosslinked ultrasound-responsive hyaluronic acid hydrogel comprises the following steps:

[0009] (1) Dissolving hyaluronic acid in a phosphate buffer solution with a pH of 5.5, then adding 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide (EDC) and N-hydroxysuccinimide ester (NHS), stirring evenly, adding dopamine hydrochloride, stirring evenly under nitrogen protection, adjusting the pH to 5-5.5, reacting at room temperature overnight, collecting the reaction product for dialysis, and finally vacuum freeze-drying to obtain hyaluronic acid dopamine;

[0010] (2) copolymerizing 4-vinylphenylboronic acid with polyethylene glycol methacrylate to obtain a block polymer poly(polyethylene glycol methacrylate-co-4-vinylphenylboronic acid);

[0011] (3) mixing and dissolving hyaluronic acid dopamine and block polymer poly(polyethylene glycol methacrylate-co-4-vinylphenylboronic acid) in deionized water to obtain a mixed solution;

[0012] (4) preparing drug-loaded iron oxide nanomagnetic microbubbles, and then adding them to the mixed solution of step (3), stirring evenly, to obtain a hydrogel solution;

[0013] Furthermore, in step (4), the preparation method of the drug-loaded iron oxide nanomagnetic microbubbles is as follows: 0.6 mg / mL of the drug solution to be loaded, 10 mM sodium dodecyl sulfate aqueous solution and 2-10 mg / mL Fe304 aqueous solution are prepared respectively, and then mixed in a volume ratio of 3:3:8, placed in an ice bath environment, stirred evenly with a homogenizer at a speed of not less than 20000 rpm, then allowed to stand for more than 12 hours, and then purified and washed with a magnet and deionized water for at least three times to obtain drug-loaded iron oxide nanomagnetic microbubbles.

[0014] (5) adding alkaline solution to the hydrogel solution prepared in step (4) to adjust the pH value to 5-6, mixing well and letting stand to obtain a double cross-linked ultrasound-responsive hyaluronic acid hydrogel.

[0015] Furthermore, in step (1), the molecular weight of the hyaluronic acid is 200,000-400,000.

[0016] Furthermore, in step (1), the dialysis uses a dialysis bag with a molecular weight cutoff value of 35KD, and the vacuum freeze-drying temperature is -80°C and the time is 48 to 96 hours.

[0017] Furthermore, in step (1), the molar ratio of hyaluronic acid, 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide, N-hydroxysuccinimide ester and dopamine hydrochloride is 1:1:2:1.

[0018] Furthermore, in step (2), the preparation method of the block polymer poly(ethylene glycol methacrylate-co-4-vinylphenylboronic acid) is as follows: 191.8 mg of 4-vinylphenylboronic acid, 2.4 mL of polyethylene glycol methacrylate, and 10 mg of initiator are added to a container containing 3.5 mL of 1,4-dioxane, and the mixture is evenly mixed to obtain a reaction solution. Nitrogen is introduced into the container and stirred continuously. The reaction solution is heated to 80° C. After stirring for reaction, the reaction product is precipitated in n-hexane and then redissolved in 1,4-dioxane. The precipitation and dissolution operations are repeated 3 times. Finally, the precipitate is vacuum dried overnight to obtain the block polymer poly(polyethylene glycol methacrylate-co-4-vinylphenylboronic acid).

[0019] Furthermore, in step (3), in the mixed solution, the mass concentration of hyaluronic acid dopamine is 50 mg / mL, and the mass concentration of block polymer poly(polyethylene glycol methacrylate-co-4-vinylphenylboronic acid) is 75 mg / mL.

[0020] Furthermore, in step (4), the added amount of the drug-loaded iron oxide nanomagnetic microbubbles is 50 mg / mL.

[0021] Application of the double cross-linked ultrasound-responsive hyaluronic acid hydrogel prepared by the above method in drug delivery.

[0022] Beneficial effects of the present invention:

[0023] 1) The present invention provides a method for preparing a double cross-linked ultrasound-responsive hyaluronic acid hydrogel, using hyaluronic acid as the main material, grafting catechol groups onto the main chain of HA through amide reaction for functional modification, introducing boric acid groups to form borate bonds with catechol as the first cross-link of the gel, and at the same time embedding bubbles wrapped with iron oxide nanoparticles loaded with drugs in the gel, and utilizing the covalent action formed by catechol groups and iron oxide nanoparticles as the second cross-link of the gel. The drug-loaded bubbles of the iron oxide nanoparticles wrapped therein act as an ultrasonic response unit, which can cause stable vibration of the bubbles under the action of ultrasound, thereby releasing the drugs and iron oxide nanoparticles on the surface, and realizing ultrasonically controlled drug release.

[0024] 2) The present invention innovatively proposes a double cross-linking strategy, which significantly improves the performance of the hydrogel. In terms of mechanical strength, traditional single hyaluronic acid hydrogels often have problems with insufficient mechanical strength and elasticity, and it is difficult to meet the needs of certain specific application scenarios. However, through the double cross-linking strategy of the present invention, the mechanical strength of the hydrogel is enhanced. Under the same test conditions, the modulus of the traditional single cross-linked hyaluronic acid hydrogel is 100-500Pa, while the modulus of the hydrogel prepared by the double cross-linking strategy of the present invention is significantly increased to 1000Pa to 1200Pa. This significant modulus improvement not only improves the structural stability of the hydrogel, but also may enhance its applicability in biomedical applications such as myocardial repair.

[0025] 3) The double-crosslinked ultrasound-responsive hyaluronic acid hydrogel of the present invention can release drugs through ultrasound and has a good release effect.

[0026] 4) The double-crosslinked ultrasound-responsive hyaluronic acid hydrogel of the present invention has a simple structure design, a wide source and low cost.

[0027] 5) The material used in the double-crosslinked ultrasound-responsive hyaluronic acid hydrogel of the present invention has the characteristics of low toxicity and good biocompatibility, and has a good application prospect in the field of biological applications. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 is the ultraviolet spectrum of the hyaluronic acid dopamine prepared in Example 1;

[0029] Figure 2 The Raman spectra of the hydrogels prepared in Example 1 and Comparative Examples 1-2;

[0030] Figure 3 This is a scanning electron micrograph of the double cross-linked ultrasound-responsive hyaluronic acid hydrogel prepared in Example 1;

[0031] Figure 4The rheological characteristic curves of the hydrogels prepared in Example 1 and Comparative Examples 1-2;

[0032] Figure 5 The drug release rate test results of the double cross-linked ultrasound-responsive hyaluronic acid hydrogel prepared in Example 1;

[0033] Figure 6 This is a fluorescence confocal three-dimensional imaging image of cell adhesion of the double-crosslinked ultrasound-responsive hyaluronic acid hydrogel prepared in Example 1;

[0034] Figure 7 The cytotoxicity test results of the double cross-linked ultrasound-responsive hyaluronic acid hydrogel prepared in Example 1. DETAILED DESCRIPTION

[0035] The technical solution of the present invention is further described below in conjunction with the accompanying drawings and specific embodiments.

[0036] Example 1

[0037] A method for preparing a double-crosslinked ultrasound-responsive hyaluronic acid hydrogel comprises the following steps:

[0038] (1) 1 g of hyaluronic acid (molecular weight of 300,000) was dissolved in 100 mL of phosphate buffer solution with a pH of 5.5, and then 338 mg of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide (EDC) and 405 mg of N-hydroxysuccinimide ester (NHS) were added. After stirring, 2.358 g of dopamine hydrochloride was added. The molar ratio of hyaluronic acid, 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide, N-hydroxysuccinimide ester and dopamine hydrochloride was 1:1:2:1. After stirring under nitrogen protection, the pH was adjusted to 5-5.5 with hydrochloric acid or sodium hydroxide. The pH value was maintained unchanged for half an hour, and the reaction was continued at room temperature overnight. The reaction product was collected, dialyzed using a dialysis bag with a molecular weight cutoff of 35 KD, and finally freeze-dried at -80°C for 72 hours to obtain hyaluronic acid dopamine;

[0039] (2) 191.8 mg of 4-aminostyrene-1-carboxylate, 2.4 mL of polyethylene glycol methacrylate, and 10 mg of an initiator (azobisisobutyronitrile) were added to a flask containing 3.5 mL of 1,4-dioxane, and ultrasonically treated for 2 min to obtain a reaction solution. Nitrogen was introduced into the container for 30 min with continuous stirring. The reaction solution was heated to 80° C. and stirred for reaction. The reaction product was precipitated in n-hexane and then redissolved in 1,4-dioxane. The precipitation and dissolution operations were repeated 3 times. Finally, the precipitate was vacuum dried overnight to obtain a block polymer poly(polyethylene glycol methacrylate-co-4-vinylphenylboronic acid).

[0040] (3) 50 mg of hyaluronic acid dopamine and 75 mg of block polymer poly(polyethylene glycol methacrylate-co-4-vinylphenylboronic acid) were mixed and dissolved in 1 mL of deionized water to obtain a mixed solution;

[0041] (4) First, prepare 0.6 mg / mL of the drug to be loaded (HSA human serum albumin modified with Cy5.5) solution, 10 mM sodium dodecyl sulfate aqueous solution and 6 mg / mL Fe304 aqueous solution, then mix them in a volume ratio of 3:3:8, place them in an ice bath environment, stir them with a homogenizer at a speed of not less than 20,000 rpm for 1-3 minutes, then let them stand for more than 12 hours, and then purify and wash them with a magnet and deionized water for at least three times to obtain drug-loaded iron oxide nanomagnetic microbubbles; add the drug-loaded iron oxide nanomagnetic microbubbles to the mixed solution of step (3) at an addition amount of 50 mg / mL, stir them evenly, and obtain a hydrogel solution;

[0042] (5) Add 1 mol / L sodium hydroxide solution to the hydrogel solution prepared in step (4) until the pH value of the system is 5-6, mix well and let stand to obtain a double cross-linked ultrasound-responsive hyaluronic acid hydrogel.

[0043] Figure 1 This is the ultraviolet spectrum of the hyaluronic acid dopamine prepared in Example 1. It can be seen that compared with dopamine, the hyaluronic acid dopamine has a peak at a wavelength of 276nm near the characteristic peak of the dopamine catechol group at 280nm, thereby determining that the hyaluronic acid dopamine is successfully synthesized.

[0044] Comparative Example 1

[0045] A preparation method of a hyaluronic acid dopamine hydrogel comprises the following steps: dissolving 1 g of hyaluronic acid (molecular weight of 300,000) in 100 mL of a phosphate buffer solution with a pH of 5.5, then adding 338 mg of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide (EDC) and 405 mg of N-hydroxysuccinimide ester (NHS), stirring evenly, adding 2.358 g of dopamine hydrochloride, stirring evenly under nitrogen protection, adjusting the pH to 5-5.5 with hydrochloric acid or sodium hydroxide, maintaining the pH value unchanged for half an hour, and then continuing the reaction at room temperature overnight, collecting the reaction product, and dialyzing it with a dialysis bag with a molecular weight cutoff of 35 KD to obtain the hyaluronic acid dopamine hydrogel.

[0046] Comparative Example 2

[0047] A method for preparing a single cross-linked hyaluronic acid hydrogel: The preparation of hyaluronic acid dopamine and block polymer poly (polyethylene glycol methacrylate-co-4-vinylphenylboronic acid) is the same as in Example 1. 50 mg of hyaluronic acid dopamine and 75 mg of block polymer poly (polyethylene glycol methacrylate-co-4-vinylphenylboronic acid) are mixed and dissolved in 1 mL of deionized water to obtain a mixed solution, and 1 mol / L sodium hydroxide solution is added until the pH of the system is 5-6. After mixing evenly, the mixture is allowed to stand to obtain a mixed solution.

[0048] Figure 2 The Raman spectra of the hydrogels prepared in Example 1 and Comparative Examples 1-2 are shown in the figure. It can be seen from the figure that the hyaluronic acid dopamine hydrogel, the single cross-linked hyaluronic acid hydrogel and the double cross-linked ultrasound-responsive hyaluronic acid hydrogel prepared in Example 1 are all at 1250-1500 cm -1 The characteristic peak of benzene ring vibration is observed at 550-650cm in the double cross-linked ultrasound-responsive hyaluronic acid hydrogel prepared in Example 1. -1 The catechol-iron coordination effect.

[0049] Figure 3 This is a scanning electron micrograph of the double cross-linked ultrasound-responsive hyaluronic acid hydrogel prepared in Example 1. Figure 3 It can be seen that the hydrogel is filled with a large number of interconnected irregular pores and has a porous structure.

[0050] 1. The rheological properties of the hydrogels prepared in Example 1 and Comparative Examples 1-2 were tested using a rheometer, and a fixed strain dynamic frequency sweep test was performed at 25° C. using a 25 mm parallel plate in a frequency range of 0.1 to 100 rad / s and a strain of 1%.

[0051] Figure 4 The rheological characteristic curves of the hydrogels prepared in Example 1 and Comparative Examples 1-2 are as follows: Figure 4 It can be seen that under the same test conditions, the modulus of the hydrogels prepared in Comparative Examples 1 and 2 is 100-500 Pa, while the modulus of the hydrogel prepared in Example 1 of the present invention is significantly increased to 1000 Pa to 1200 Pa. This significant increase in modulus not only improves the structural stability of the hydrogel, but also may enhance its applicability in biomedical applications such as myocardial repair.

[0052] 2. Test the drug release rate of the double-crosslinked ultrasound-responsive hyaluronic acid hydrogel prepared in Example 1.

[0053] Step 1: The double cross-linked ultrasound-responsive hyaluronic acid hydrogel (loaded with HSA human serum albumin) prepared in Example 1 was placed in a glass bottle, and then ultrasound was applied using a focused ultrasound transducer. The ultrasound frequency was adjusted to a range of 400 to 800 kHz using a functional generator, and the amplitude was set to 20 Vpp. Ultrasound was applied using a focused ultrasound transducer, and the time of each ultrasound cycle was set to 4 s, and the ultrasound cycle period was 50 cycles;

[0054] Step 2: After the ultrasonic cycle is completed, immerse in PBS, collect the supernatant after 2 hours to measure the fluorescence value of the released liquid, and use the corresponding protein detection kit to determine the quantitative released protein content.

[0055] Figure 5 This is the drug release rate test result of the double-crosslinked ultrasound-responsive hyaluronic acid hydrogel prepared in Example 1. The result shows that the drug release result is excellent and can reach 83%.

[0056] 3. Test the biocompatibility of the double cross-linked ultrasound-responsive hyaluronic acid hydrogel prepared in Example 1.

[0057] Detection method: Human umbilical vein endothelial cells (HUVEC) were cultured in DMEM medium containing 10% FBS until they were in good condition. The double cross-linked ultrasound-responsive hyaluronic acid hydrogel prepared in Example 1 was sterilized, and then the cells in the logarithmic growth phase were inoculated on the sterilized hydrogel surface at a density of 10,000 / mL and placed in an incubator at 5% CO2 and 37°C. After 24 hours, the living cells were labeled with the fluorescent dye am, the sample was taken out and rinsed with PBS, and the three-dimensional distribution image of the cells in the hydrogel was obtained by confocal microscopy, and the cell distribution and adhesion were observed to evaluate the compatibility of the hydrogel with the cells.

[0058] Figure 6 This is a fluorescent confocal three-dimensional image of cell adhesion of the double-crosslinked ultrasound-responsive hyaluronic acid hydrogel prepared in Example 1. It can be seen that the cells are evenly distributed in the hydrogel and tightly adhere to the surface and internal structure of the hydrogel, showing good cell compatibility.

[0059] 4. Test the cytotoxicity of the double cross-linked ultrasound-responsive hyaluronic acid hydrogel prepared in Example 1.

[0060] Detection method: Human umbilical vein endothelial cells (HUVEC) were cultured in a DMEM high-glucose medium (containing double antibodies) containing serum and antibiotics to the logarithmic growth phase. The hydrogel samples prepared in Example 1 and Comparative Example 2 were disinfected and sterilized, and soaked in a serum-free medium to obtain two hydrogel degradation solutions. Human umbilical vein endothelial cells were inoculated in a 96-well plate at a certain density, and an appropriate amount of cell suspension was added to each well. A blank control group and two experimental groups were set up. The blank control group was a normal culture medium group without adding a hydrogel degradation solution, and the experimental group 1 was a culture medium group with the addition of the hydrogel degradation solution of Comparative Example 2, and the experimental group 2 was a culture medium group with the addition of the hydrogel degradation solution of Example 1. The 96-well plate was placed in an incubator and cultured for 48 hours. After the culture was completed, CCK8 detection solution was added and cultured for a suitable time, and finally the absorbance value was determined using an ELISA instrument, and the cell survival rate was calculated to evaluate the cytotoxicity of the hydrogel.

[0061] Figure 7 This is the cytotoxicity test result of the double cross-linked ultrasound-responsive hyaluronic acid hydrogel prepared in Example 1. It can be seen that the double cross-linked ultrasound-responsive hyaluronic acid hydrogel prepared in Example 1 has lower cytotoxicity.

[0062] The above figures and test data fully prove that the hydrogel of the present invention has excellent mechanical properties, biocompatibility and excellent drug release performance, and the preparation process is simple and easy to operate, low cost, energy saving, and conducive to large-scale promotion and research. In addition, it provides strong support for its wide application in the biomedical field and has important research significance in the field of drug delivery.

Claims

1. A method for preparing a double cross-linked ultrasound-responsive hyaluronic acid hydrogel, characterized in that: The steps include: (1) dissolving hyaluronic acid in a phosphate buffer solution with a pH of 5.5, then adding 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide and N-hydroxysuccinimide ester, stirring evenly, adding dopamine hydrochloride, stirring evenly under nitrogen protection, adjusting the pH to 5 to 5.5, reacting at room temperature overnight, collecting the reaction product for dialysis, and finally vacuum freeze-drying to obtain hyaluronic acid dopamine; (2) copolymerizing 4-vinylphenylboronic acid with polyethylene glycol methacrylate to obtain a block polymer poly(polyethylene glycol methacrylate-co-4-vinylphenylboronic acid); (3) mixing and dissolving hyaluronic acid dopamine and block polymer poly(polyethylene glycol methacrylate-co-4-vinylphenylboronic acid) in deionized water to obtain a mixed solution; (4) preparing drug-loaded iron oxide nanomagnetic microbubbles, and then adding them to the mixed solution of step (3), stirring evenly, to obtain a hydrogel solution; (5) adding alkaline solution to the hydrogel solution prepared in step (4) to adjust the pH value to 5-6, mixing well and letting stand to obtain a double cross-linked ultrasound-responsive hyaluronic acid hydrogel.

2. The method for preparing the double cross-linked ultrasound-responsive hyaluronic acid hydrogel according to claim 1, characterized in that: In step (1), the molecular weight of the hyaluronic acid is 200,000-400,000.

3. The method for preparing the double cross-linked ultrasound-responsive hyaluronic acid hydrogel according to claim 1, characterized in that: In step (1), the dialysis uses a dialysis bag with a molecular weight cutoff value of 35KD, the vacuum freeze-drying temperature is -80°C, and the time is 48 to 96 hours.

4. The method for preparing the double cross-linked ultrasound-responsive hyaluronic acid hydrogel according to claim 1, characterized in that: In step (1), the molar ratio of hyaluronic acid, 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide, N-hydroxysuccinimide ester and dopamine hydrochloride is 1:1:2:

1.

5. The method for preparing the double cross-linked ultrasound-responsive hyaluronic acid hydrogel according to claim 1, characterized in that: In step (2), the preparation method of the block polymer poly(ethylene glycol methacrylate-co-4-vinylphenylboronic acid) is as follows: 191.8 mg of 4-vinylphenylboronic acid, 2.4 mL of polyethylene glycol methacrylate, and 10 mg of initiator are added to a container containing 3.5 mL of 1,4-dioxane, and the mixture is evenly mixed to obtain a reaction solution. Nitrogen is introduced into the container and stirred continuously. The reaction solution is heated to 80° C. After stirring for reaction, the reaction product is precipitated in n-hexane and then redissolved in 1,4-dioxane. The precipitation and dissolution operations are repeated 3 times. Finally, the precipitate is vacuum dried overnight to obtain the block polymer poly(polyethylene glycol methacrylate-co-4-vinylphenylboronic acid).

6. The method for preparing the double cross-linked ultrasound-responsive hyaluronic acid hydrogel according to claim 1, characterized in that: In step (3), in the mixed solution, the mass concentration of hyaluronic acid dopamine is 50 mg / mL, and the mass concentration of block polymer poly(polyethylene glycol methacrylate-co-4-vinylphenylboronic acid) is 75 mg / mL.

7. The method for preparing the double cross-linked ultrasound-responsive hyaluronic acid hydrogel according to claim 1, characterized in that: In step (4), the preparation method of the drug-loaded iron oxide nanomagnetic microbubbles is as follows: 0.6 mg / mL of the drug solution to be loaded, a 10 mM sodium dodecyl sulfate aqueous solution and a 2-10 mg / mL Fe304 aqueous solution are prepared respectively, and then mixed in a volume ratio of 3:3:8, placed in an ice bath environment, stirred evenly with a homogenizer at a speed of not less than 20000 rpm, then allowed to stand for more than 12 hours, and then purified and washed with a magnet and deionized water for at least three times to obtain drug-loaded iron oxide nanomagnetic microbubbles.

8. The method for preparing the double cross-linked ultrasound-responsive hyaluronic acid hydrogel according to claim 1, characterized in that: In step (4), the added amount of the drug-loaded iron oxide nanomagnetic microbubbles is 50 mg / mL.

9. Use of the double-crosslinked ultrasound-responsive hyaluronic acid hydrogel prepared by the method according to any one of claims 1 to 8 as a carrier in drug delivery.

Citation Information

Patent Citations

  • Adhesive complex coacervates and methods of making and using thereof

    CN102548581A

  • Preparation method and application of immune nano composite hydrogel with anti-tumor effect

    CN116270435A

Cited By

  • Composite modified hydrogel preparation and preparation method thereof

    CN120204125A

  • Injectable structure self-stabilizing dynamic hydrogel for combined carrying and sequential release of sinigrin and dabigatran

    CN120837509A

  • Dynamic crosslinking bio-ink as well as preparation method and application thereof

    CN122208830A